A novel strategy to avoid sensitivity loss in pooled testing for SARS-CoV-2 surveillance: validation using nasopharyngeal swab and saliva samples - Millward, Georgia G.; Popelka, Shane M.; Gutierrez, Anthony G.; Kowallis, William J.; von Tersch, Robert L.; Yerramilli, Subrahmanyam V. (Frontiers in Public Health, 2023)
At the peak of the COVID-19 pandemic, pooled surveillance strategies were employed to alleviate the overwhelming demand for clinical testing facilities. A major drawback of most pooled-testing methods is the dilution of positive samples, which leads to a loss of detection sensitivity and the potential for false negatives. We developed a novel pooling strategy that compensates for the initial dilution with an appropriate concentration during nucleic acid extraction and real-time PCR. We demonstrated the proof of principle using laboratory-created 10-sample pools with one positive and corresponding individual positive samples by spiking a known amount of heat-inactivated SARS-CoV-2 into viral transport medium (VTM) or pooled negative saliva. No Ct difference was observed between a 10-sample pool with one positive vs. the corresponding individually analyzed positive sample by this method, suggesting that there is no detectable loss of sensitivity. We further validated this approach by using nasopharyngeal swab (NPS) specimens and showed that there is no loss of sensitivity. Serial dilutions of the virus were spiked into VTM and pooled with negative saliva in simulated 10-sample pools containing one positive to determine the LOD and process efficiency of this pooling methodology. The LOD of this approach was 10 copies/PCR, and the process efficiencies are ~95%−103% for N1 and ~87%−98% for N2 with samples in different matrices and with two different master mixes tested. Relative to TaqPath 1-step master mix, the TaqMan Fast Virus 1-Step master mix showed better sensitivity for the N2 assay, while the N1 assay showed no Ct difference. Our pooled testing strategy can facilitate large-scale, cost-effective SARS-CoV-2 surveillance screening and maintain the same level of sensitivity when analyzed individually or in a pool. This approach is highly relevant for public health surveillance efforts aimed at mitigating SARS-CoV-2 spread.